Application of Project-Based Learning to Improve Critical Thinking Skills and Student Learning Outcomes in Materials on Relationship Between Economic Activities and Utilization of Natural Resources - Larina Yuliana, Elma; Agustin, Mubiar; Sujana, Atep (International Conference on Elementary Education, 2020)
This study aims to develop critical thinking skills and student learning outcomes on the subject of Natural Resources Utilization through Project-Based Learning. The research method used in this research is Classroom Action Research. The subjects of this study were the fourth grade students of SD IT Insan Rabbani for the 2018/2019 academic year, totaling 29 students. Students consist of 15 male students and 14 female students. The instruments used in this study were learning outcomes tests, critical thinking skills tests, and observation sheets. The results showed that the critical thinking skills and learning outcomes of elementary school students for grade IV on the material of the relationship between economic activities and the use of natural resources through project-based learning increased in each cycle. The results of student learning completeness in the pre-cycle are 41.38%. Through the application of project-based learning, student learning outcomes have increased in each cycle, namely 48.28% in the first cycle, the second cycle, which is 72.41% and 86.21% in the third cycle. Based on the results of these studies, it can be concluded that critical thinking skills and learning outcomes of SD IT Insan Rabbani Class IV students on the subject of Relationships between Economic Activities and Utilization of Natural Resources have increased through Project-Based Learning. Thus, the researcher recommends Project-Based Learning as an alternative in improving critical thinking skills in social studies learning material on the relationship between economic activities and the use of natural resources.